2016
DOI: 10.1111/eve.12523
|View full text |Cite
|
Sign up to set email alerts
|

Case series evaluating the use of absorbable staples compared with metallic staples in equine ventral midline incisions

Abstract: The objective was to evaluate the use of subcuticular absorbable staples (SAS) and compare them with metallic staples (MS) in abdominal skin closure for equine abdominal surgery in terms of surgical site infection (SSI) reduction. A prospective, randomised clinical trial was carried out on client owned horses presenting for abdominal surgery (n = 42 horses). During surgery, horses were randomly assigned to receive either SAS or MS. Preoperative criteria recorded included age, breed and sex of horse; surgical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Several suture types used for subcutaneous or skin closure have been associated with incisional complications. Stainless steel staples for skin closure and polyglycolic acid in the subcutaneous layer were identified as a risk factors for surgical site infections 9,59 . Antibiotic‐coated polyglactin 910 in the subcutaneous layer did not diminish the risk of surgical site infection 60 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several suture types used for subcutaneous or skin closure have been associated with incisional complications. Stainless steel staples for skin closure and polyglycolic acid in the subcutaneous layer were identified as a risk factors for surgical site infections 9,59 . Antibiotic‐coated polyglactin 910 in the subcutaneous layer did not diminish the risk of surgical site infection 60 .…”
Section: Introductionmentioning
confidence: 99%
“…Antibiotic‐coated polyglactin 910 in the subcutaneous layer did not diminish the risk of surgical site infection 60 . Subcuticular absorbable staples were used with superior wound scores compared to conventional stainless steel staples and may be an alternative skin closure technique in some equine hospitals 59 …”
Section: Introductionmentioning
confidence: 99%
“…Seven original studies [368][369][370][371][372][373][374] and three narrative reviews focussed exclusively on complications after abdominal surgery, mainly colics [23][24][25]. Anaesthetic-related mortality rates up to seven days after surgery is higher in colics compared with elective procedures (11.7 versus 0.9%) [1].…”
Section: Other Factorsmentioning
confidence: 99%
“…Biedrzycki and Brounts [118] reported that the INSORB stapler performed well in closing skin incisions following exploratory celiotomy surgeries in horses. The SAS allowed natural wound drainage, which contributed to low incidences of wound infection.…”
Section: Zinc As Absorbable Staplementioning
confidence: 99%
“…The staples were deemed insufficient in strength to retain revascularization edema that resulted in an open wound and to a higher-than-normal wound infection rate (average = 15%). In veterinary medicine, Biedrzycki and Brounts [118] reported that the INSORB stapler was found difficult to use in some parts of the horse with excessively thick tissues. The firm tissues prevented the stapler from firing, and the tissue capture necessary for staple deployment was not achieved.…”
Section: Zinc As Absorbable Staplementioning
confidence: 99%